Dongeng Antikorupsi Sebagai Bahan Literasi Bagi Peserta Didik di Sekolah Dasar - Atikah Mumpuni; Rizki Umi Nurbaeti (Jurnal Ilmiah Wahana Pendidikan, 2020)
Corruption reflects a character that indicates a person's dishonesty. Eradicating corruption in this case must be balanced with the provision of anti-corruption education to prevent future corruption. One form of anti-corruption education in elementary schools that can be implemented is through fairy tales. The aim of this study was to develop anti-corruption tales that are appropriate and readable by students, so that they can be used as literacy material in elementary schools. The type of this study was research and development type. Data collection in this study was carried out through interviews, questionnaires, and tests. The conclusion obtained as a result of the research showed that anti-corruption tales developed as literacy materials for elementary school students were considered feasible in good categories after validation tests were carried out by material experts, media experts, and practitioners. The readability of the product is seen from the ability of students to understand the anti-corruption tale text which was developed after a product trial was carried out and assessed in the good category (for low-grade students) and in the very good category (for high-grade students).